2020
DOI: 10.14569/ijacsa.2020.0110665
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Detection and Prevention of Web Vulnerabilities

Abstract: The Internet provides a vast range of benefits to society and empowers the users in a variety of ways to use web applications. Simply, the internet has become the most transformative and fast-growing technology ever built, but it also brings new security challenges to web services in internet applications because of the scattered and open nature of the internet. A simple vulnerability in the program code could favor/benefit an attacker to obtain unauthorized access and perform adversary actions. Hence, the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…These include normal, error-based double query, and blind injection techniques, empowering attackers to manipulate database queries and potentially compromise sensitive data. It underscores the importance of robust security measures such as code audits, input validation, and the adoption of secure coding practices to mitigate these threats effectively [3], [4]. High detection accuracy machine language algorithms (MLA) can guarantee detection being achieved in real-time [5].…”
Section: Related Workmentioning
confidence: 99%
“…These include normal, error-based double query, and blind injection techniques, empowering attackers to manipulate database queries and potentially compromise sensitive data. It underscores the importance of robust security measures such as code audits, input validation, and the adoption of secure coding practices to mitigate these threats effectively [3], [4]. High detection accuracy machine language algorithms (MLA) can guarantee detection being achieved in real-time [5].…”
Section: Related Workmentioning
confidence: 99%
“…Manual code analysis in the security context involves performing code vulnerability checks during peer code reviews [10]. Automated code analysis at the development stage is performed using static analysis tools that scan the code for vulnerabilities without executing the code [11], [13], [26].…”
Section: Development Phasementioning
confidence: 99%
“…Amir Manzor et al [26] presented a literature survey recapitulating security solutions and major vulnerabilities to promote further research by establishing a system of the existing methods on a bigger horizon. They suggested that there is no way to alleviate all the web vulnerabilities; therefore, further study is desirable in web information security.…”
Section: Literature Reviewmentioning
confidence: 99%